2017
DOI: 10.2319/032717-214.1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of Class II malocclusion cases treated with miniscrew-anchored Forsus Fatigue Resistant Device: A randomized controlled trial

Abstract: Class II correction was mainly dentoalveolar in both treatment groups. Use of miniscrews with Forsus did not enhance mandibular forward growth nor prevent labial tipping of the mandibular incisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 23 publications
(65 reference statements)
8
58
2
3
Order By: Relevance
“…However, the decrease in SNA angle was greater in the control group (−0.96°) compared with the skeletal anchorage group. Eissa et al 30 and Aslan et al 18 also reported values similar to Elkordy et al 28 in which they had a greater decrease in SNA angle and increase in SNB angle in the skeletal anchorage groups compared with the control groups.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…However, the decrease in SNA angle was greater in the control group (−0.96°) compared with the skeletal anchorage group. Eissa et al 30 and Aslan et al 18 also reported values similar to Elkordy et al 28 in which they had a greater decrease in SNA angle and increase in SNB angle in the skeletal anchorage groups compared with the control groups.…”
Section: Resultsmentioning
confidence: 63%
“…Elkordy et al 28 and Turakhraman et al 29 reported significant increase in mandibular length with skeletal anchorage (4.05 and 3.69 mm respectively). Eissa et al 30 reported an increase of 1.03 mm when used along with skeletal anchorage but was not clinically significant when compared to the control group (0.61 mm).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…14 TADs can be easily placed clinically in one appointment by the orthodontist with no need for complicated surgical procedures to facilitate safe and precise implant placement or to connect it to the teeth. Eissa et al 15 recently reported the use of a miniscrew-anchored Forsus in correction of Class II malocclusion. However, there is no evidence in the literature supporting the clinical effectiveness of miniscrew-anchored fixed functional appliances for the treatment of Class III malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated based on an alpha significance level of 0.05 and a beta of 0.2 to detect a mean difference of 2mm with a standard deviation of 1.5mm in the changes in mandibular length between the pretreatment and posttreatment stages 18 . The results showed that a minimum of 12 patients were needed in each group; to increase the test power even more, it was decided to select 32 patients for the treatment group.…”
Section: Methodsmentioning
confidence: 99%